Algerbra 1

posted by .

1/3x + 5/6 = 2/9x - 1/3

How do I solve this to get the answer?


For basic algebra you need to understand that we can add (or subtract) the same quantity from both sides without affecting the = sign. We can also multiply and divide (except by 0) both sides without affecting the = sign.
For this equation
1/3x + 5/6 = 2/9x - 1/3 add -1/3x to both sides to get
5/6 = 2/9x - 1/3 - 1/3x then add 1/3 to both sides to get
5/6 + 1/3 = 2/9x - 1/3x
Now factor x from the right hand side to get
5/6 + 1/3 = x(2/9 - 1/3)
Then divide both sides by (2/9 - 1/3) to get
(5/6 + 1/3)/(2/9 - 1/3) = x
The rest is arithmetic and you should be able to do that.



There is a much easier way to do that.
You don't need to factor anything.

Just get the like quantities on the same side like so,

(5/6+1/3)=(2/9x-1/3x) then
7/6=-1/9x and solve from there.



Amanda, there are probably a dozen "equivalent" ways to do this problem. I was trying to explain the steps I was doing.
And yes, if we have 2/9x-1/3x we would think of it as
x(2/9-1/3)
You simply combined the terms, so the distributive property was used implicitly. That's all. I didn't 'factor', I separated out the common term of two terms. This is just the reverse of the distributive property.
I see you caught your arithmetic error too. Good job.


I also see you didn't have any arithmetic error, excuse me.
Another poster had a typo, but they still had the correct answer.
Never mind


WHY rational expressions that are being added must have an LCD, but rational expressions that are being multiplied do not need to have an LCD.


solve for x if 4(2x-3)+32=60


And now I see I did use the word factor. I probably shouldn't have used that term because it's typically reserved for polynomials. Oh well...
However when you combined the terms this is exactly what you did too.


1/3x-2/9x=-5/6-1/3
1/9x=-7/6
x=-7/6 * 9
x=-10 1/2


1/3x-2/9x=-5/6-1/3

1/9x=-7/6
5/6-1/3=5/6-2/6=3/6=1/2 not -7/6 so
x=9*1/2=9/2
Check my arithmetic


Do it like this,
2/9x-1/3x=5/6+1/3

Do you see how I moved the like quantaties to the same side?

Trust me I am in Geometry and passed Algebra with flying colors.

  • Algerbra 1 -

    -(ab/6c)5

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. more math

    solve this equation: 6x+7=8x-13 ....plz Tell what you don't understand so that we may help you. Subtract 6x from both sides of the equation and see what you get. Then add 13 to both sides. If you do it right, that will be the answer.
  2. algebra

    1 1 7 -y - -= - 2 8 8 please help me! It isn't clear to me what this expression means. Can you clarify it?
  3. algerbra 1

    what is the answer to 5x-16=14-5x Just giving you the answer is not what this forum is about. We'd be defeating the purpose of you assignment by doing that. Try to work the variables to one side, say the lefthand side, and the numbers …
  4. algebra

    I need a step by step explanation on how to add these two equations 2x+3y=1 5x+3y=16 Subtract the first equation from the second. (Subtract left and right sides separately). This gives you 3x = 15 Then divide both sides by 3. x = 5 …
  5. Algebra

    Can someone verify if my answers are correct?
  6. Algebra

    Select all the statements that can be used as steps to solve the equation 6[4(2x−1)]=80−8. Subtract 8 from 80. Combine 80 and 6. Multiply 2x and -1 by 4. Subtract 1 from both sides of the equation. Add 4 to both sides of …
  7. ALGEBRA

    Select all the statements that can be used as steps to solve the equation 6[4(2x−1)]=80−8. Subtract 8 from 80. Combine 80 and 6. Multiply 2x and -1 by 4. Subtract 1 from both sides of the equation. Add 4 to both sides of …
  8. Pre-Algebra

    How do you solve 4x+4=9x-36? I understand that you need to get the variables alone but to I add or subtract 9x to both sides?
  9. Algebra

    Which of the following describes a correct method for solving the equation below?
  10. algerbra

    am i correct on this? question: solve and check square of 5x+6 is equal to x work and answer: square each side 5x+6=x^2 subtract 5x-6 on both sides 0=x^2-5x-6 (x+1)(x-6) x+1=0 subtract -1 on each side x= -1 is a reject x-6=0 add 6

More Similar Questions